Crosstalk of DNA Methylation Triggered by Pathogen in Poplars With Different Resistances - Xiao, Dandan; Zhou, Ke; Yang, Xiaoqian; Yang, Yuzhang; Ma, Yudie; Wang, Yanwei (Frontiers in Microbiology, 2021)
DNA methylation plays crucial roles in responses to environmental stimuli. Modification of DNA methylation during development and abiotic stress responses has been confirmed in increasingly numbers of plants, mainly annual plants. However, the epigenetic regulation mechanism underlying the immune response to pathogens remains largely unknown in plants, especially trees. To investigate whether DNA methylation is involved in the response to infection process or is related to the resistance differences among poplars, we performed comprehensive whole-genome bisulfite sequencing of the infected stem of the susceptible type Populus × euramerican ‘74/76’ and resistant type Populus tomentosa ‘henan’ upon Lonsdalea populi infection. The results revealed that DNA methylation changed dynamically in poplars during the infection process with a remarkable decrease seen in the DNA methylation ratio. Intriguingly, the resistant Populus tomentosa ‘henan’ had a much lower basal DNA methylation ratio than the susceptible Populus × euramerican ‘74/76’. Compared to mock-inoculation, both poplar types underwent post-inoculation CHH hypomethylation, however, significant decreases in mC and mCHH proportions were found in resistant poplar. In addition, most differentially CHH-hypomethylated regions were distributed in repeat and promoter regions. Based on comparison of DNA methylation modification with the expression profiles of genes, DNA methylation occurred in resistance genes, pathogenesis-related genes, and phytohormone genes in poplars during pathogen infection. Additionally, transcript levels of genes encoding methylation-related enzymes changed during pathogen infection. Interestingly, small-regulator miRNAs were subject to DNA methylation in poplars experiencing pathogen infection. This investigation highlights the critical role of DNA methylation in the poplar immune response to pathogen infection and provides new insights into epigenetic regulation in perennial plants in response to biotic stress.